Cervical Disc Arthroplasty Versus Anterior Cervical Discectomy and Fusion for Incidence of Symptomatic Adjacent Segment Disease: A Meta-Analysis of Prospective Randomized Controlled Trials. Issue 19 (1st October 2016) - Zhu, Yuhang; Zhang, Boyin; Liu, Haochuan; Wu, Yuntao; Zhu, Qingsan
Abstract : Study Design: Meta-analysis of randomized controlled trials. Objective: To evaluate the reported rate of adjacent segment disease (ASD) of cervical disc arthroplasty (CDA) compared with anterior cervical discectomy and fusion (ACDF). Summary of Background Data: Motion-maintaining technologies such as CDA have developed rapidly because of the concern of ASD. Till date, however, it still has been under debate whether CDA is superior to ACDF regarding the incidence of ASD. Methods: We comprehensively searched PubMed, EMBASE, and Cochrane Central Register of Controlled Trails for prospective randomized controlled trials (RCTs) that reported the incidence of ASD between CDA and ACDF. The retrieved results were last updated on November 20, 2015 without language restrictions. Two independent authors selected qualified studies, assessed methodological quality, and extracted requisite data. Results: Fourteen relevant RCTs involving 3235 individuals with a follow-up period of 2 to 7 years were included in the meta-analysis (1696 in CDA group and 1539 in ACDF group). The outcomes indicated that CDA was superior to ACDF considering the lower rate of ASD (risk ratio, 0.57; 95% confidence interval, 0.37 to 0.87; P = 0.009). And compared with ACDF, there were significantly fewer adjacent segment reoperations in the CDA group (risk ratio, 0.47; confidence interval, 0.32 to 0.70; P = 0.0002). Subgroup analysis stratified by different types of disc prostheses was also performed. Conclusion: CDA was superior to ACDF regarding fewer ASDs and relative reoperations on the basis of available evidence from a meta-analysis of 14 RCTs. CDA may be a better surgical procedure to reduce the incidence of ASD for patients with cervical disc disease compared with ACDF. Further well-designed studies should continue to pay attention to excellent patients with longer-term follow-up to evaluate the incidence of ASD of these two procedures. Level of Evidence: 1